Pathogenic variability in Bipolaris sorokiniana isolates obtained from cereal hosts - and SATVINDER KAUR, ANJU BALA* (Indian Phytopathology, 2010)
Thirty different isolates of Bipolaris sorokiniana were obtained from infected leaf samples of bread wheat, durumÂ wheat, barley, triticale and rye leaves collected randomly from Gurdaspur, Ludhiana and Ferozepur (Abohar, Fazilka) areasrepresenting foothills, central and Southwestern parts of Punjab state. Pathogenic variabilty was studied on a set of 12commercial and susceptible varieties of bread wheat, durum wheat, barley, triticale as well as rye and Phalaris minor at seedlingÂ stage and flag leaf stage. The isolates were grouped into 8 and 12 clusters on the basis of host response at seedling stage andÂ flag leaf stage respectively. Based on cluster analysis of average virulence indices obtained at seedling stage and flag leafÂ stage, three clusters were formed which divided the isolates into three pathotypes. Isolates from durum wheat and rye hostsÂ were clustered in most virulent pathotype group whereas isolates obtained from bread wheat and triticale hosts were scatteredÂ in all the three pathotype groups indicating maximum variability in these isolates.